Farm - Smith, Emma; Barnard,Lucy; Baldwin, Hannah (Haywards Health, UK: iSeek Ltd, 2019)
An interactive farm adventure for young children, helping them count animals from 1 to 10 by lifting flaps to find the hidden animals.
Boad book with lift-the-flap features.
"Learn countion to 10"-Cover
Keywords: Counting -- Juvenile literature; Farm life -- Juvenile literature